Disturbance and climate affect species richness and aboveground biomass relationship in a forest–savanna transition ecosystem - Nyako, Melanie C.; Libalah, Moses B.; Kabelong, Louis-Paul-Roger B.; Momo, Stéphane T.; Babonguen, Marius G.; Djouking, Cyntia K.; Ekué, Marius R.M.; Fabo, Laure B.; Fomekong, Alex B.T.; Guedje, Nicole M.; Madountsap, Tagnang N.; Medou, Adrian; et al. (Elsevier, 2024)
The relationship between species richness and aboveground biomass (richness–biomass relationship) is a major facet of ecosystem functions and has stimulated debates over the past decades. However, we still lack basic knowledge on whether this relationship has consistent patterns across natural and human-impacted vegetation cover types. More importantly, the effects of disturbance and climatic conditions on species richness and aboveground biomass remain controversial. Using data from 197 0.5-ha plots established within a forest-savanna transition ecosystem, we determined three ecological vegetation covers via non-metric multidimensional scaling, obtained gridded climate data and calculated disturbance index from species succession guilds. We examined the consistency of the richness–biomass relationship across the vegetation covers using general linear models and further analysed the effects of disturbance and climatic conditions on this relationship using non-mixed and mixed linear models. We identified three vegetation cover types corresponding to Old-growth forests, Cocoa agroforests and Woodland savannas, suggesting a succession gradient from late-, mid-, and early-successions, respectively. Aboveground biomass consistently increased with species richness across the three vegetation cover types (i.e. positive relationship). Species richness interacts with climate humidity to increase aboveground biomass while interaction of species richness and disturbance rather decreases aboveground biomass consistently across the vegetation cover types. Our results provide insights into the relationship between diversity and ecosystem functions, having implications for ecosystem restoration and understanding ecological consequences of disturbance and climate change in the forest-savanna ecosystem.